Observations on Growth and Development of Bambusa Arundinacea - Tomar, M.S. (Indian Forester, 1963)
Observations on growth and development of rhizomes and new culms of Bambusa arundinacea were recorded. The rhizome is closely similar in essential structure to the culm and has got nodes and internodes. It bears buds and covered profusely with scales. There is no terminal bud in culm. The height growth is caused by the successive elongation of the internodes. Several internodes from the bottom upwards grow simultaneously. The internodes become visible above the edges of the sheaths after they have completed about 65 per cent of their potential length. Basal portion of an internode is the most active growing region and continues growing until maximum growth is reached. Removal of sheaths from young internodes reduced the potential length of these internodes. The growth rate of new culms is slow, i.e., 2"-3" per day in the intial stages but increases to about 10" after the culms have attained a height of over 5 ft. Maximum growth recorded in 24 hours was 13 inches